PERVASIVE CRYSTALLIZATION OF ANTIGORITE IN NORTHERN APENNINE OPHIOLITES: THE EXAMPLE OF MONTECARELLI PERIDOTITES (TUSCANY, CENTRAL ITALY) - Frassi, Chiara; Chighine, Gianfranco; Mauro, Daniela; Biagioni, Cristian; Zaccarini, Federica; Marroni, Michele (Ofioliti, 2022)
The occurrence of pervasive crystallization of antigorite associated to brittle tectonics is described for the first time in the External Ligurian peridotites of the Northern Apennine (Italy). Antigorite was found in a slide block of subcontinental peridotites included in the tectonized sedimentary mélange of the Leo Unit (western External Ligurian units). This mélange, as those from the External Ligurian units, originated in Santonian-early Campanian time span from a source area corresponding to the Ocean-Continent Transition Zone at the Adria plate margin. The antigorite was found within veins belonging to four systems, from V1 to V4, each characterized by different attitude and morphology. The morphology of the veins ranges from massive to fibrous, with the latter characterized by fibers both parallel and perpendicular to the vein walls. Rare occurrence of chrysotile and calcite were identified within the veins. The antigorite crystallization in the peridotites cannot be interpreted as related to an orogenic high-pressure metamorphism but most likely can be regarded as developed at shallow structural level in the late stage of the rifting phase when subcontinental mantle was progressively exposed at the surface, intruded by gabbro bodies, and cut by basaltic dykes